Pemanfaatan E-Commerce sebagai Media Pembelajaran Kewirausahaan: Systematic Literature Review - Prasetyo, Edo Bagus; Veri, Jhon (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The advancement of information and communication technology has brought significant changes in the educational landscape, particularly in entrepreneurship learning which now demands more adaptive and digitally oriented approaches. This study aims to systematically review the utilization of e-commerce as a medium for entrepreneurship education in the context of digital transformation. The research method applied is a Systematic Literature Review (SLR) using the PRISMA approach, with literature sourced from Google Scholar and Scopus through the Publish or Perish application for the period of 2022–2025. From a total of 200 articles initially identified, 70 were selected based on inclusion and exclusion criteria. Bibliometric visualization using VOSviewer was employed to map thematic relationships and identify research clusters. The results indicate that e-commerce significantly contributes to entrepreneurship learning, especially in supporting practice-based education, digital literacy, and curriculum innovation in higher education. Three major clusters were identified: digital technology development, integration of technology in education, and higher education transformation. This study concludes that e-commerce serves not only as a teaching tool but also as a key catalyst in shaping a sustainable digital entrepreneurship education ecosystem.